The great seducer: Cleopatra, queen and sex symbol - Pina Polo, Francisco; Knippschild, Silke; García Morcillo, Marta (London; New York, NY: Bloomsbury, 2013)
The image of Queen Cleopatra is above all that of a great seducer who used seduction to achieve power, and whose own power could in turn be seductive. Most ancient sources, from the triumph of Augustan propaganda onwards, propagated negative characteristics of her as a ‘femme fatale’ who could manipulate at will the great Roman imperatores of the Late Republican period, Julius Caesar and Mark Antony. Thus, for instance, Horace describes Cleopatra as a fatale monstrum, while Lucan does not hesitate to discredit her by calling her ‘Egypt’s shame; fury of Latium; to the bane of Rome unchaste’. The descriptions of how the Egyptian queen appeared unexpectedly before Caesar, wrapped in a carpet or bundled up in some clothes, or how she met Antony (on Antony and Cleopatra from Antony’s perspective see also the article by Marta García Morcillo in this volume) , surrounded by luxury and exoticism as if...
Keywords: Cleopatra -- VII, -- Reina de Egipto; Poder; Reinas; Sexualidad